Penguatan Pendidikan Karakter Melalui Internalisasi Profil Pelajar Pancasila Pada Siswa Kelas 3 (Studi di SDN 1 Popongan) - Eni Setyaningsih (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
The aim of this study is to find out what activities are carried out to strengthen character education with the internalization model of Pancasila student profiles in grade 3 students at SDN 1 Popongan. This research is a descriptive research. Through several steps from collecting data, analyzing data, interpreting data to drawing conclusions. Data obtained through observation and documentation. The results of the research show that in grade 3 SDN 1 Popongan in strengthening character education through several methods such as exemplary, habituation, giving directions/warnings and motivation. There are activities carried out by the grade 3 students which indicate an internalization of the values ​​of the Pancasila student profile, namely morning literacy activities, class pickets and being with the school environment.The dimensions of values ​​reflected in these activities include having a noble character, global diversity, mutual cooperation, independence, critical and creative reasoning.